Sistemas de gestão ambiental ISO 14001: implementar ou não? Uma proposta para a tomada de decisão - Moretti, Giuliano Nacarato (2007)
The adoption of the ISO 14001 standard to establish a certified environmental management system (EMS) is not compulsory. Organizations seeking to implement an EMS can opt for the ISO 14001 requirements, as well as their own criteria and requirements. If this last option is chosen, it is not possible to certify such system, as those criteria and requirements cannot be compared with a standard previously established. One of the difficulties of the decision making process, is that lay entrepreneurs may find themselves incapable of finding enough subsidies for the decision of adopting or not the standard. The present work presents a tool that facilitates corporate decision making, providing a thorough analysis of the real necessity and feasibility of the implementation of the ISO 14001 standard and the respective certification. This tool consists of a multicriterial analysis, in which is possible to verify the compatibility between the organizational profile (defined by the decision maker) and the ISO 14001 standard. This organizational profile takes into account cultural, environmental, managerial and economic-financial features of the organization. The algorithm considers criteria and subcriteria (motivations of organizations which might conduct to the implementation of the standard), such as: market, legal compliance, environmental control, investments and resources, functional (staff) and institutional image, which are presumed o be influenced by the standard. The presented tool promotes parities prioritizations between such motivations, through a process known as Analytic Hierarchy Process (AHP), and also scores the organizational profile in relation to the characteristics of the standard, providing a recommendation for its possible adoption. This recommendation of adopting or not the ISO 14001 standard seeks to facilitate the organization decision making; and, as a result, it also enhances the chances of the organization attaining its objectives.